Recording the optimistic. An audiovisual approach to the city of Lisbon by its architecture school in the 1980s - Matos Silva, Leonor (2017)
With the revolution of 25April 1974, Portugal initiated a unique cultural journey that had, in the architectural field, a parallel with the questioning of the modern movement, conveyed by Second World War aftermath. The academic context was a particularly opportunity for this mirroring criticism. The director of the Lisbon architecture course would then have for banner an engagement in “a sort of counter-culture”; however, the cultural critique that happened would be more of a fortunate accident. In fact, an optimistic post-traumatic euphoria was a common trace of some of the most radical pedagogical experiences that took place. Standing before the ‘creative’ productions that unfolded under the Lisbon architecture school in the 1980s, we acknowledge an unconventional form of expression that leads us to question whether a particular framed identity marked Portuguese architectural culture ever since. This paper aims to fundament such claim by recurring to primary sources not yet disclosed – namely testimonies and documents – that relate directly to Lisbon’s architecture course between 1976 and 1986, configuring the background research for a PhD; in the analysis here presented, three videos from the school’s archives will be examined, and their pertinence, while cultural urban components, will be revealed.